2020
DOI: 10.1016/j.isci.2020.101576
|View full text |Cite
|
Sign up to set email alerts
|

Fast Heat Transport Inside Lithium-Sulfur Batteries Promotes Their Safety and Electrochemical Performance

Abstract: Summary Lithium-sulfur batteries are paid much attention owing to their high specific capacity and energy density. However, their practical applications are impeded by poor electrochemical performance due to the dissolved polysulfides. The concentration of soluble polysulfides has a linear relationship with the internal heat generation. The issue of heat transport inside lithium-sulfur batteries is often overlooked. Here, we designed a functional separator that not only had a high thermal conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…The chemical states of compositional elements were studied with X-ray photoelectron spectroscopy (XPS). 37 In particular, deconvoluted Fe 2p spectrum showed that Fe 3+ 2p 1/2 (724.6 eV) and 2p 3/2 (711.2 eV) were dominant over Fe 2+ 2p 1/2 (728.2 eV) and 2p 3/2 (714.6 eV) ( Figure 2G ), which is consistent with the unimmobilized FeOCl crystal ( Figure S3 ). XPS analyses of other elements in the FeOCl/Al 2 O 3 composite and the γ-Al 2 O 3 support are shown in Figures S13 and S14 .…”
Section: Resultssupporting
confidence: 77%
“…The chemical states of compositional elements were studied with X-ray photoelectron spectroscopy (XPS). 37 In particular, deconvoluted Fe 2p spectrum showed that Fe 3+ 2p 1/2 (724.6 eV) and 2p 3/2 (711.2 eV) were dominant over Fe 2+ 2p 1/2 (728.2 eV) and 2p 3/2 (714.6 eV) ( Figure 2G ), which is consistent with the unimmobilized FeOCl crystal ( Figure S3 ). XPS analyses of other elements in the FeOCl/Al 2 O 3 composite and the γ-Al 2 O 3 support are shown in Figures S13 and S14 .…”
Section: Resultssupporting
confidence: 77%
“…In Figure b, the peaks at 652.7 and 641.1 eV are typically assigned to the Mn 2p 1/2 and Mn 2p 3/2 with two satellite peaks at 657.6 and 645.4 eV, respectively, indicating the oxidation state of Mn 2+ . , Figure c shows the S 2p XPS spectrum which can be decomposed as four peaks, representing three types of sulfur species. These two characteristic peaks at 162.1 and 160.9 eV are correspondingly ascribed to the S 2p 1/2 and S 2p 3/2 , while the others at 163.6 and 162.5 eV are corresponding to satellite peak and C–S bonding, revealing that sulfur is doped into the carbon structure during the CVD process. ,, By virtue of the Gaussian fitting method, the C 1s original curve is deconvoluted into three sub-peaks placed at 285.5, 284.7, and 284.4 eV (Figure d), each belonging to C–S–C, C–C, and CC bonds. , The existence of C–S–C bonding is consistent with the analysis of the S 2p peak, further proving S-doping in the carbon structure. In contrast, the XPS analysis of the MCO sample also reveals that Mn and Co elements exist in the chemical states of Co 2+ and Mn 2+ as metal oxides (Figure S4), which proves the correctness of the HRTEM analysis result.…”
Section: Resultsmentioning
confidence: 99%
“…Coating materials on separators can chemically adsorb the escaped lithium polysulfides, [ 131 ] catalyze sulfur reduction, [ 132 ] and enhance the heat transfer inside Li‐S batteries. [ 133 ] Furthermore, the coating materials can prevent the blocking of open pores by solid electrolytes and the impaling of separators by the lithium dendrite; thus, they enhanced the safety for Li‐S batteries [ 131 ] during cycling at high current densities.…”
Section: Li‐s Batteriesmentioning
confidence: 99%